A PENGEMBANGAN SISTEM INFORMASI TAGIHAN AIR BERSIH DESA - Imam, M. Imam Fathulloh Al Bahri (JATISI, 2024)
The Community-Based Drinking Water and Sanitation Provision Program (PAMSIMAS) is a government initiative that focuses on a community approach in providing clean water and sanitation. One of the institutions involved, the Drinking Water and Sanitation Facilities Management Group (KP SPAM), is responsible for the management and maintenance of clean water supplies at the village level. However, KP SPAM faces problems in recording and processing monthly payment data because of the manual system used. This research aims to develop a web-based clean water bill payment information system using PHP and MySQL. The waterfall method is applied in system development, with Blackbox Testing to ensure the software functions as required. This system is expected to increase operational efficiency and reduce the risk of errors and delays in processing monthly bills. This web-based clean water bill payment information system has been successfully implemented.